1996
DOI: 10.1017/s0016756800008657
|View full text |Cite
|
Sign up to set email alerts
|

Glacial or non-glacial origin for the Bigganjargga tillite, Finnmark, northern Norway

Abstract: Bigganjargga is the classic locality for the Varangian ice age in northern Scandinavia. The presence of two sets of striations on the underlying quartzite basement has been taken as evidence for a glacial origin of the Bigganjargga diamictite. However, soft-sediment surface structures on the underlying sandstone indicate that it was not consolidated when the diamictite was emplaced. Together with structures in the diamictite this shows that the deposit formed as a debris flow moving northwestwards over an unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 16 publications
0
58
0
Order By: Relevance
“…They were not observed in the area by Jensen & Wulff-Pedersen (1996), Arnaud & Eyles (2002) or by myself. None are found on gneisses and sandstones, but quartzite pebbles are reported to display striations (Bjørlykke, 1967), and other striated clasts have been recorded from Viernjárga (Edwards, 1975) and the Mortensnes Formation (Edwards, 1984).…”
Section: Diamict Macrotextures and Striated Clastsmentioning
confidence: 67%
See 4 more Smart Citations
“…They were not observed in the area by Jensen & Wulff-Pedersen (1996), Arnaud & Eyles (2002) or by myself. None are found on gneisses and sandstones, but quartzite pebbles are reported to display striations (Bjørlykke, 1967), and other striated clasts have been recorded from Viernjárga (Edwards, 1975) and the Mortensnes Formation (Edwards, 1984).…”
Section: Diamict Macrotextures and Striated Clastsmentioning
confidence: 67%
“…However, others have suggested that there possibly was no glacial influence at all (except maybe from sea ice) for deposits which are considered to display the best proof of glaciation (e.g., Jensen & Wulff-Pedersen, 1996, 1997Arnaud & Eyles, 2002). Mainly the pavements and diamictites are taken as evidence of glacial action, and most other geological data are interpreted in that context.…”
Section: Varangerfjord Diamictitesmentioning
confidence: 99%
See 3 more Smart Citations